Frühe Šaiḫī- und Bābī-Theologie : Die Darlegung der Beweise für Muḥammads besonderes Prophetentum (Ar-Risāla fī Iṯbāt an-Nubūwa al-Ḫāṣṣa) - Eschraghi, Armin (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
This book is an introduction to the literature and thought of the founders of the Shaykhiyya and the Bābiyyah, two important religious movements in nineteenth-century Iran. The first part is an overview of the thought of Aḥmad al-Aḥsāʾī and Kāẓim ar-Rashtī, the progenitors of the Shaykhiyya, with a focus on their religious and philosophical teachings. The second part is an analysis of the early writings of ʿAlī-Muḥammad Shīrāzī (the Bāb), the initiator of the Bābiyyah. It contains a survey of major concepts found in his works and addresses issues that have generated debate in the past, particularly the exact nature of his religious claim and its reception by his contemporaries. Finally, the book contains an edition of the Bāb's Treatise on Specific Prophethood. This is the first scholarly edition of a work by the Bāb to be published in the original language.